Thermal behavior of copper(II) pseudohalide complexes containing bidentate amines - Sargentelli, V.; Mauro, A. E.; Netto, AVD; Mattioli, MPD; Nogueira, V. M.; Neto, VAD (Kluwer Academic Publ, 2002)
Pseudohalide complexes of copper(II) with aliphatic bidentate amines, [Cu(N-3)(2)(N,N-diEten)](2) 1, [Cu(NCO)(2)(N,N-diEten)](2) 2, [Cu(NCO)(2)(N,N-diMeen)](2) 3, [Cu(N-3)(NCS)(N,N'-diMeen)](2) 4 and [Cu(N-3)(NCO)(N,N-diMeen)](2) 5 (N,N-diEten=N,N-diethylethylenediamine; N,N-diMeen=N,N- dimethyl-ethylenediamine and N,N'-diMeen = N,N'-dimethylethylenediamine), were prepared, characterized and their thermal behavior was investigated by TG curves. According to thermal analysis and X-ray diffraction patterns all compounds decomposed giving copper(II) oxide as final product. The mechanisms of decomposition were proposed and an order of thermal stability was established.
Keywords: bidentate amines; copper; infrared spectroscopy; pseudohalide; synthesis; thermal analysis